2019
DOI: 10.1590/1677-5449.190063
|View full text |Cite
|
Sign up to set email alerts
|

Existe concordância entre as culturas de osso e tendão em pacientes com lesões profundas de extremidades?

Abstract: Resumo Contexto As infecções profundas de extremidades representam um desafio para o salvamento de membro dos pacientes. Objetivos Investigar se existe concordância entre as culturas de osso e tecido profundo em pacientes com lesões tróficas de extremidades. Métodos Foi realizado um estudo retrospectivo incluindo 54 pacientes com lesões tróficas profundas de extremidades internados, no Complexo Hospitalar Universitário Professor Edgard Santos, Salvador (BA), Brasil. Foram incluídos todos os pacientes que re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
(24 reference statements)
0
1
0
1
Order By: Relevance
“…When the culture is obtained from deep tissue and a single pathogen grows, it may suggest the etiology of the associated bone infection, although studies have found a correlation between soft tissue and bone cultures in < 50% of cases, being as low as 17.4% in some cases. 145 , 146 Thus, in most cases material should be collected aseptically, surgically, or percutaneously due to the reliable results. 147 Acute infections of lesser severity that have not undergone previous treatment can be considered for empirical treatment without culture collection, although culture collection should be performed or repeated when the clinical course is unfavorable or when the ulcer is subject to surgical debridement (recommendation class IIa, level of evidence C).…”
Section: Chapter 5 Diagnosing and Treating Foot Infections In People ...mentioning
confidence: 99%
See 1 more Smart Citation
“…When the culture is obtained from deep tissue and a single pathogen grows, it may suggest the etiology of the associated bone infection, although studies have found a correlation between soft tissue and bone cultures in < 50% of cases, being as low as 17.4% in some cases. 145 , 146 Thus, in most cases material should be collected aseptically, surgically, or percutaneously due to the reliable results. 147 Acute infections of lesser severity that have not undergone previous treatment can be considered for empirical treatment without culture collection, although culture collection should be performed or repeated when the clinical course is unfavorable or when the ulcer is subject to surgical debridement (recommendation class IIa, level of evidence C).…”
Section: Chapter 5 Diagnosing and Treating Foot Infections In People ...mentioning
confidence: 99%
“…Já as culturas de tecidos moles devem ser coletadas de todas as feridas e de forma asséptica (curetagem ou biópsia) para direcionamento do tratamento. Quando obtidas de tecidos profundos com crescimento de patógeno único, podem sugerir etiologia da infecção óssea associada, porém há que se considerar que estudos demonstram correlação da cultura de tecidos moles e óssea em menos de 50% dos casos, chegando em algumas casuísticas até 17,4% 145 , 146 . Por esse motivo, na maioria dos casos é sugerida a coleta de material de forma asséptica, via cirúrgica ou via percutânea, a qual também apresenta resultados fidedignos 147 .…”
Section: Capítulo 5 Diagnóstico E Tratamento De Infecção Nos Pés De P...unclassified